Parental Perspectives on Financial Incentives for Adolescents: Findings From Qualitative Interviews - Kera M. Beskin MPH, MBA; Rachel Caskey MD, MAPP (SAGE Publishing, 2019)
Background. Financial incentives are becoming more common to promote health behaviors; however, little is known about the acceptability of incentivizing adolescent health behaviors. Design. Qualitative semistructured phone interviews were conducted with 26 parents who had participated in a research study involving incentivizing a recommended, preventive adolescent health behavior (human papillomavirus vaccination). Data were coded and analyzed to identify themes. Interview domains included the following: preferred incentive distribution, ideal financial incentive amount, and general reactions to economic incentives for preventative services. Results . Parents held positive perceptions about incentives and most parents felt that the incentive could be provided directly to their adolescent child, rather than to the parent. Parents stated several benefits from incentivizing adolescent health behavior including creating an opportunity to teach their child about money, reimbursing families for time and effort, and motivating the adolescent to complete the health behavior. Topics for consideration when providing cash incentives to adolescents included the adolescent's maturity level, parents' desire to monitor adolescent's spending, and parents' want to remain involved in health care and financial decisions for their adolescent. Conclusions . This study demonstrates the potential for parental acceptance of financial incentives for adolescent health behaviors and explores areas of parental concern around financial incentives, which could help inform future health care-based incentive programs.